Pengaruh Struktur Modal terhadap Kinerja Perusahaan Non Keuangan yang Terdaftar Di BEI - Silvia Juni Shaputri; Seto Sulaksono Adi Wibowo (Politeknik Negeri Batam, 2016)
This study aimed to determined the effect of capital structure to the firm performance. Firm performance is the firm ability to manage and allocate existing resources. Firm has a good performance if firm has a proportion of optimal capital structure. This study use four capital structure measure are short-term debt (STD), long-term debt (LTD), total debt to total asset (TDTA) and total debt to total equity (TDTQ) and three performance measure are return on asset (ROA), return on equity (ROE) and earning per share (EPS). This study included 196 non-financial companies listed on Indonesian Stock Exchange over the period of 2013-2014. Data Panel regression that used in this study not found impact of capital structure that measure using STD, LTD, TDTA and TDTQ to the firm performance that measure using ROA, ROE and EPS.